(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
From the importance of knowledge in the speech, we knew the importance of oral exam. So in this paper we integrated BOW (Bag of Word), LSA(Latin Semantic Analysis), ASR (automatic speech recognition), zero crossing rate, and Ontology based approach to automate the online oral exam especially in Arabic language with take into consideration the authentication problem. Our proposal method faced many challenges in Arabic language because there isn’t semantic dictionary like WordNet in English and HowNet in Chinese. Also Arabic language has complicated synonyms. Our proposal can help improving meaningfulness. Finally, the proposed method in this paper didn’t forget automation the feedback for determining learning disability